STREAMLINING DIGITAL CORRELATION-INTERFEROMETRIC DIRECTION FINDING WITH SPATIAL ANALYTICAL SIGNAL - Smailov, Nurzhigit; Tsyporenko, Vitaliy; Sabibolda, Akezhan; Tsyporenko, Valentyn; Abdykadyrov, Askar; Kabdoldina, Assem; Dosbayev, Zhandos; Ualiyev, Zhomart; Kadyrova, Rashida (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
This study investigated a search-free digital method for radio direction-finding that utilizes spatial analytical signal reconstruction. The research focused on optimizing the method's accuracy for estimating the direction of a radio source. The analysis identified the separation distance and number of chosen antenna elements for signal reconstruction as the key parameters influencing accuracy. Analytical optimization and simulations were employed to determine the optimal values for these parameters. The research successfully modeled the impact of antenna element selection on direction-finding errors under specific signal-to-noise conditions. This model can be used to guide further development and optimization of this radio direction-finding method.